David Barker: the revolution that anticipates existence - Italo Farnetani; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2014)
David Barker is the man who "anticipated" the existence of babies by focusing attention on the importance of the fetus and what takes place during intrauterine life. Barker was one of the physicians who in the last decades brought about the greatest changes in medicine, changes so important as to represent a veritable revolution in medical thought. According to Barker's studies, the embryo obviously has a genetic complement coming from the mother and father, but from the very first stages of development it begins to undergo the influence of the outside environment, just as occurs for adults whose biological, psychological and pathological aspects are influenced by the environment to a not well-established percentage between genetic complement and epigenetics. Much of our future lives as adults is decided in our mothers' wombs. If Barker's discovery was revolutionary from the cultural standpoint, it was even more so from the strictly medical one. Barker's research method was rigid from the methodological standpoint, but innovative and speculative in its working hypotheses, with a humanistic slant. Barker's idea has another practical corollary: it is evident that the role of obstetricians, perinatologists and neonatologists is more and more relevant in medicine and future prevention. Unquestionably, besides the enormous merits of his clinical research, among the benefits that Barker has contributed there is that of having helped us to see things from new points of view. Not only is the neonate (and even more so the fetus) not an adult of reduced proportions, but perhaps the neonate is the "father" of the adult person.